(untitled) (Research, Society and Development, 2021)
Secondary disorders in consequences to diabetes involves the development of several diseases in the oral cavity, as periodontitis, xerostomy, infection by diverse pathogens and dysfunctions on the salivary secretion. These alterations occur partially, in consequence of the oxidative stress occasioned by hyperglycemia, and are important in patients undiagnosed or that have flaws in their therapeutic process. The aim of this work was to evaluate biochemical alterations of submandibular glands in response to oxidative stress during diabetes mellitus, and verify the effects of N-acetylcystein supplementation to diabetic rats, specially on the regulation of modifications related to glutathione and thiol proteins. For this purpose, the levels of some oxidative stress markers and the occurrence of the post-translational event of S-glutathionylation were evaluated. The a-amilase degranulation by isolated acinar cells and glandular relative weight was also measured for each experimental group. The compound was able to decrease the lipoperoxidation and proteic oxidation observed in the submandibular gland of diabetic rats, preventing the decrease of the tecidual reducing power and increasing the occurrence of the post-translational process of S-glutathionylation. The diabetic condition increases the degranulation of a-amilase and the glandular weight, but the supplementation with N-acetylcystein did not affect these events. Together these findings may help to elucidate the status of oxidative stress on salivary glands and suggest new therapeutic strategies employing antioxidants of low molecular weight to prevent oral and systemic dysfunctions related to diabetes.